1995
DOI: 10.3109/00016489509139407
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Rhinometry in the Pre-operative Assessment of Adenoidectomy Candidates

Abstract: Claims have been made for the potential of acoustic rhinometry (AR) in the evaluation of adenoidectomy patients. Little evidence has been presented to support such claims, and evidence is accumulating that AR is inaccurate in reflecting anatomical reality in the nasopharynx. We set out to establish whether acoustic rhinometry studies could predict operative decision-making sufficiently for it to be of assistance to the clinician, despite these theoretical and practical obstacles. A total of 101 patients aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
8

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
8
0
8
Order By: Relevance
“…The accuracy of this technique for measuring nasopharyngeal cross-sectional areas may be re®ned, to some extent, using topical nasal decongestant solutions prior to acoustic measurements [5]. Some investigators have reported improved acoustic measurements of the nasal cavity using contoured nasal adapters.…”
Section: Discussionmentioning
confidence: 98%
“…The accuracy of this technique for measuring nasopharyngeal cross-sectional areas may be re®ned, to some extent, using topical nasal decongestant solutions prior to acoustic measurements [5]. Some investigators have reported improved acoustic measurements of the nasal cavity using contoured nasal adapters.…”
Section: Discussionmentioning
confidence: 98%
“…In this examination, the mean change of value of nasopharyngeal volume (NPV) was estimated. In accordance with the literature, it was assumed that the most representative section of the rhinometric curve is a 4 cm section situated at a distance of 6-12 cm from the front nostril [4][5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…Fisher et al 12 referem que a RA não tem acurácia para evidenciar pequenas alterações de volume na nasofaringe e conclui que a RA tem pouco valor preditivo se usada isoladamente para avaliar a presença de adenóide hipertrófica; terá maior poder preditivo se avaliarmos conjuntamente com o quadro clínico.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Embora a RA tenha menor precisão para medir as dimensões da nasofaringe devido à existência de obstruções severas anteriores causando subestimação de regiões posteriores, aos movimentos voluntários e involuntários do palato mole, ao escape sonoro para a fossa nasal oposta e às próprias limitações físicas da técnica 5,12,14,15 , ela foi capaz de evidenciar o ganho de ASTM e volume pérveo na nasofaringe após a cirurgia.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified